2011
DOI: 10.1111/j.1365-2109.2010.02787.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein-to-energy ratio on reproduction in female redclaw crayfish Cherax quadricarinatus

Abstract: The e¡ect of eight diets with di¡erent protein-to-energy ratios (P^E ratio 510, 11, 14, 16, 18, 20, 22, 24 mg kJ À 1 ) on reproduction of female redclaw cray-¢sh Cherax quadricarinatus was tested under laboratory conditions. After 75 days, there was a signi¢cant e¡ect of the P^E ratio on ¢nal weight, spawning females and the number of juveniles per female. Using the broken-line and quadratic equations, optimal values for the P^E ratio were: 16.0, 17.1 and 16.0 mg kJ À 1 . The P^E ratio signi¢cantly a¡ected p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A P:E ratio of 16.4 ± 0.6 mg kJ −1 in diets for female red claw crayfish increases the number of spawnings and juveniles per female, suggesting a better use of dietary energy (Rodríguez‐González et al . ). The highest final weight of juveniles that we obtained is higher than the weight reported by Pérez‐Medina (), who obtained 0.56–0.8 g after 62 days of cultivation using a commercial diet.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A P:E ratio of 16.4 ± 0.6 mg kJ −1 in diets for female red claw crayfish increases the number of spawnings and juveniles per female, suggesting a better use of dietary energy (Rodríguez‐González et al . ). The highest final weight of juveniles that we obtained is higher than the weight reported by Pérez‐Medina (), who obtained 0.56–0.8 g after 62 days of cultivation using a commercial diet.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies, broodstock diet, in terms of protein and lipid levels given to spawners would influence reproductive performance (gonad maturation, number of spawns per female, fecundity) and early offspring quality (egg development, biochemical composition) (Rodríguez‐González ; Rodríguez‐González et al . , ). However, there are no studies that measured the influence of broodstock diet on further stages.…”
Section: Introductionmentioning
confidence: 99%
“…(, ) who found that diets with 26–33% P optimized growth and survival of juvenile and pre‐adult stages of the redclaw crayfish. Rodríguez‐González, Villarreal, Hernández‐Llamas, García‐Ulloa, Vazquez‐Boucard and Serrano‐Pinto () reported that the protein to energy ratio for optimum reproduction was 18 ± 2 mg kJ −1 . The present study shows that there is an interaction between dietary protein and lipid level causing specific effects on lipid accumulation in the hepatopancreas and changes in GSI.…”
Section: Discussionmentioning
confidence: 99%
“…The protein requirement for good growth and efficient food conversion (food conversion ration: FCR = Feed Given / Animal Weight Gain) in redclaw has received considerable attention, with a number of studies identifying optimal protein inclusion rates in the diet (Cortés-Jacinto et al 2003, 2004a, 2004bMuzinic et al 2004;Thompson et al 2004;Campaña-Torres et al 2005;Cortes-Jacinto et al 2005;Thompson et al 2005;Rodríguez-González et al 2006;Thompson et al 2006;Metts et al 2007;Pavasovic et al 2007b;Saoud et al 2008;Zenteno-Savín et al 2008;Cortés-Jacinto et al 2009;Rodríguez-González et al 2009a;Gutiérrez and Rodríguez 2010;Garza de Yta et al 2011;Rodríguez-González et al 2011;Arredondo-Figueroa et al 2013;Stumpf et al 2014;Ranjan and Bavitha 2015) that are specific to the life history stage of the crayfish (Cortés-Jacinto et al 2009). These studies indicate that the protein requirement falls as redclaws age.…”
Section: Nursery Dietmentioning
confidence: 99%